Eurotopians fragments of a different future - Diehl, Johanna 1977-; Maak, Niklas 1972- (Hirmer, 2017)
How do we want to live? Where, at a time of profound social challenges, can we find ideas for tomorrow‘s houses and cities? For their Eurotopians project, Niklas Maak and Johanna Diehl met utopian architects who still lived in their experimental buildings from the 1960s and ’70s – and who continue to work on the ideas for a future architecture.